Legenda Etiologis Desa Simo, Kali Buthek, Kali Pepe, Desa Ngaru-ngaru dalam Babad Demak: Kajian Arkeptipal - Dhananjaya Sajjana Adhiwijna (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2025)
In Babad Demak I, written by Raden Tumenggung Suryadi in 1835 in Java (Rasa-bahning-slireng-rat) or 1906 AD, there exists an ancient etiological legend from Boyolali Regency. This legend, which dates back to the 15th century, explains the origins of several place names, including Simo Village, Buthek River, Pepe River, and Ngaru-ngaru Village. The story is closely linked to Sunan Kudus’s journey, undertaken at the command of Sultan Bintara of the Demak Sultanate, to punish and execute Ki Ageng Kebo Kenanga in Pengging Village. These toponyms Simo Village, Buthek River, Pepe River, and Ngaru-ngaru Village can be traced along a historical route stretching from the northern part of Boyolali Regency, passing through Karanggede, Klega, Simo, Banyudana, and Pengging. This study employs the theory of etiological legends, which explores the origins of names, whether of places or people. Methodologically, it adopts an archetypal approach that integrates literary and anthropological perspectives. The archetypal approach (arche) focuses on origins, primal causes, authenticity, patterns, and fundamental models. By synthesizing literary and anthropological methodologies, this research seeks to uncover the deeper cultural and historical significance of these legends within literary texts.